RELATIONSHIP OF DISCIPLINE AND LEADERSHIP WITH EMPLOYEE PERFORMANCE (CASE STUDY PT. SAMSUNG ELECTRONICS INDONESIA SURABAYA REGION) - Anggiezka Natalita Angelica; Hermin Tridayanti (NAROTAMA UNIVERSITY, Indonesia, 2019)
Discipline and leadership are the two main factors for companies to improve employee performance. Because without discipline and leadership it will produce unsatisfactory results. This study aims to determine and analyze the significant positive relationship between the discipline and leadership variables with the performance of employees at PT. Samsung Electronics Indonesia Surabaya Region. Data collection was carried out by distributing questionnaires to 50 employees of PT. Samsung at WTC (World Trade Center) Surabaya and interviewed employees directly. The research method uses the Rank Spearman correlation. The result of this research is that discipline and leadership have a positive and significant relationship with employee performance. Companies must pay attention to the discipline and leadership that the company has and improve it to improve the quality of employee performance for the better.